Exploring the link between physical activity and quality of life among university students - Mohammed, Redhwan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to examine the relationship between physical activity (PA) and quality of life (QoL) among university students, considering several factors: gender, specialization, academic level, and place of residence. This was a cross-sectional descriptive quantitative study. The study sample consisted of 302 university students from Dar Al-Uloom University in Saudi Arabia. Of these participants, 170 were males (56.58%) and 132 were females (43.42%). QoL was assessed using the WHOQOL-BREF, and PA levels were measured with the short form of the International Physical Activity Questionnaire (IPAQ). The study showed that university students were generally physically active throughout the week, and their overall QoL was ranked ‘high’, especially in areas such as life meaning, personal needs, and mood. QoL was higher among females and first-year students (p ≤ 0.05), while no differences were found based on college or residence (p > 0.05). PA was positively associated with QoL, with all correlations being statistically significant (p ≤ 0.05) and ranging from r = 0.549 to r = 0.767, indicating that higher levels of PA are strongly associated with higher perceived QoL. In conclusion, PA is an essential aspect of maintaining good health and well-being, and it is positively associated with QoL.